Mandible reconstruction with free fibula flaps: Outcome of a cost-effective individual planning concept compared with virtual surgical planning. Issue 8 (August 2017) - Rommel, Niklas; Kesting, Marco Rainer; Rohleder, Nils Hagen; Bauer, Florian Martin Josef; Wolff, Klaus-Dietrich; Weitz, Jochen
Abstract: Purpose: The free osteomyocutaneous fibular flap has become one of the primary options for mandibular reconstruction, because of the later introduction and development of virtual surgical planning (VSP). However, VSP is associated with high additional pre-operative effort and costs. Therefore, the purpose of the study was to develop a new individual cost-effective pre-operative planning concept for free fibula mandible reconstruction and to compare it with VSP regarding clinical parameters and post-operative outcome. Materials and methods: 31 patients undergoing mandibular reconstruction with a microvascular free fibular flap were divided into two groups and retrospectively reviewed. For the first group A (18 of 31 patients), an individual method with stererolithographic (STL) models, silicon templates and hand-made cutting guides was used (about 250 € planning costs/patient). For the second group B (13 of 31 patients), VSP including pre-fabricated cutting guides was used (about 2500 € planning costs/patient). Results: We found no statistically significant differences with respect to intra-operative time of mandibular reconstruction, duration of hospitalisation or post-operative complications between the two groups ( p ≥ 0.05). Conclusion: The surgical outcomes and operative efficiency of this individual and cost-effective planning concept are comparable with the much more expensive complete VSP concept.